Amalan Fatwa di Malaysia: Antara Keterikatan Mazhab dan Keperluan Tarjih - Abd.Rahman, Noor Naemah (Jurnal Fiqh, 2007)
The Enactment of Islamic Administration in the state of Malaysia has earmarked that the teaching of Shafi’ite is the main reference in issuing a fatwa. In spite of this, several changes happened in the sequence of fatwa references to fulfill the societies daily livehood especially towards the public interest. These changes proved through an observation toward the fatwas that have been issued. And soon after year 1990`s, mazhab Shafi`ite seem not to be significant, although the domination are still everlasting. In this article examples has been selected to prove this matter until there is a conclusion that indicates the practice of tarjih among the teaching of Ahl al-Sunnah wa al-Jamaah which have been significantly used in the latest fatwa.